Involvement in Specific HIV Risk Practices among Men Who Use the Internet to Find Male Partners for Unprotected Sex. (25th March 2013) - Klein, Hugh
Abstract : Purpose . Men who have sex with other men (MSM) account for more than one-half of all new HIV infections in the USA. This study reports on the prevalence of a variety of HIV risk behaviors in one specific subpopulation of risk-seeking MSM. Methods . The study was based on a national sample of 332 MSM who use the Internet to find partners for unprotected sex. Data collection was conducted via telephone interviews between January 2008 and May 2009. Results . Unprotected oral and anal sex was commonplace among study participants. Men engaged in a large number of other risky behaviors as well, including having had multiple recent sex partners (mean number = 11), simultaneous double-penile penetration of the anus (16%), eating semen out of another man's anus (17%), engaging in multiple-partner sexual encounters (47%), engaging in anonymous sex (51%), and having sex while "under the influence" (52%). Conclusions . HIV intervention and prevention programs need to address numerous behaviors that place MSM at risk for contracting/transmitting HIV. Merely focusing on unprotected anal sex does a disservice to members of this community, who typically engage in many types of behavioral risks, each of which requires addressing if HIV transmission rates are to be reduced.